The Swipe to Spend Era: An Analysis of Technology Acceptance Factors Influencing TnG E-Wallet Usage in Daily Consumer Spending - Lyn Liq Ooi; Odebunmi Abayomi Tunde; Wai Ee Leong; Han Wen Leong; Ai Hua Lew; Jia Xin Leng; Tanishq Tanishq; Daisy Mui Hung Kee (The Global Academia Publisher, 2026)
Touch ‘n Go (TnG) is an e-wallet service widely used in Malaysia, especially after the COVID-19 pandemic. E-wallets have become increasingly popular worldwide as a convenient digital payment method. This study examines the key factors influencing TnG e-wallet usage in their daily spending, as well as the relationship between continuous usage intention and continuous usage behaviour. The specific objectives are to assess the impact of facilitating conditions, perceived ease of use, perceived risk, perceived trust, and social influence; evaluate how these factors affect users’ continued usage intention; and analyze the relationship between continuous usage intention and continuous usage behaviour in the context of the TnG e-wallet service. Data were collected from 150 university students in Malaysia using a purposive sampling method. A quantitative research approach was employed through an online survey distributed to TnG e-wallet users. The findings indicate that perceived ease of use and social influence have a positively significant influence on users’ continued usage intention. The findings are anticipated to provide valuable insights for e-wallet providers to enhance user acceptance, thereby promote sustained usage behaviour.